Leveraging mechanobiology and biophysical cues in lung organoids for studying lung development and disease - Shao, Ziming; De Coppi, Paolo; Michielin, Federica (Frontiers in Chemical Engineering, 2023)
Lung organoids have emerged as powerful tools for studying lung distal diseases by recapitulating the cellular diversity and microenvironment of the lung tissue. This review article highlights the advancements in leveraging mechanobiology and biophysical cues in lung organoid engineering to improve their physiological relevance and disease modelling capabilities. We discuss the role of mechanobiology in lung development and homeostasis, as well as the integration of biophysical cues in the design and culture of lung organoids. Furthermore, we explore how these advancements have contributed to the understanding of lung distal diseases pathogenesis. We also discuss the challenges and future directions in harnessing mechanobiology and biophysical cues in lung organoid research. This review showcases the potential of lung organoids as a platform to investigate the underappreciated impacts of biophysical and biomechanical properties in enhancing lung organoids complexity and functionality, and ultimately provide new insight into embryonic lung development and pulmonary distal diseases pathogenesis.